School Natural Resource Management Education: Utilization of Breadfruit Leaves as Skin Soap Products at SDN Kutisari 2 Surabaya - Surya Andhini; Raya Sulistyowati; Khoirotul Amaliyah; Emi Supriharti (Jurnal Kemitraan Masyarakat, 2024)
This study explores the potential of breadfruit leaves (Artocarpus altilis) as a raw material in making skin care soap. Breadfruit leaves are known to contain active compounds such as saponins and flavonoids that have antibacterial, antiviral, and antioxidant properties. This study aims to test the effectiveness of breadfruit leaf extract in improving the quality of skin care soap. In addition, this study also highlights the use of breadfruit trees at SDN Kutisari 2 Surabaya, which is one of the Adiwiyata schools. This school utilizes the environment as a means of learning and maintaining the existence of plants, including breadfruit trees, which function as a source of food and traditional medicine. The results showed that soap with breadfruit leaf extract had better cleaning quality and hydrating ability compared to soap without extract. These findings indicate that breadfruit leaves can be a useful ingredient in making skin care products, as well as providing inspiration for the development of more natural and effective soap products, and supporting efforts to conserve natural resources in the school environment.